Conditions favoring biomechanically driven CV co-occurrence in lexicons. (March 2016) - Albano, Eleonora C.
Abstract: After having received serious consideration in the 1990s, the hypothesis that biomechanics is phonologized into probabilistic phonotactics subsided for methodological difficulties, while related child language studies gained ground. This paper aims at restoring the original adult language orientation of the discussion of biomechanically driven consonant–vowel co-occurrence. It presents new, detailed evidence on two languages, British English and Brazilian Portuguese, where there is clear lexical support for two CV co-occurrence biases attributable to biomechanics: a trend for the combination of coronal consonants with front vowels, and a trend against the combination of dorsal consonants with front vowels. It also shows that such biases are stronger under conditions that complicate speech planning. The analysis uses log-linear modeling in conjunction with other statistical techniques to assure comparability with previous studies and reliability of multiple comparisons. Low overall effect sizes indicate that biomechanically driven CV biases only weakly affect free combination. However, under such complicating conditions as repetition or lack of stress combined with occlusion/obstruence in initial position, effect sizes grow and significant factor interactions emerge, suggesting that such biases help simplify speech planning. Revisiting the phonologization of biomechanics hypothesis with today׳s tools supports it sufficiently to justify further pursuit and search for explanations. Highlights: New tools can now clarify long-pending issues on CV co-occurrence in lexicons. They were applied to large databases of British English and Brazilian Portuguese. Coronals and dorsals show consistent biomechanically driven biases. Such biases interact with conditions that complicate speech planning. Likely causes are synergy, co-articulation resistance and complexity of initiation.